The Effect of Student Teams Achievement Division (STAD) Learning Model and Social Skills on the Critical Thinking Ability in Four Grade Students of SD Negeri 05 Pauh Lubuk Sikaping - Reviva Safitri; Edy Syahputra; Asmin Asmin (BIRCU, 2020)
This study aims to: (1) To find out the differences of mathematical critical thinking ability of students taught with the STAD type cooperative learning model compared to conventional learning models; (2) To find out the difference of mathematical critical thinking ability of students who have high social skills compared to students who have low social skills; and (3) To find out the interaction between learning models and social skills in effecting the students' critical thinking ability. The population in this study were all grade four students at SD Negeri 05 Pauh Lubuk Sikaping, the number of students was 54, consisting of four grade A and four grade B. Data collection techniques used in this study were social skills questionnaires and critical thinking skills tests. The data analysis technique used in this study was inferential statistical techniques. Hypothesis testing is done by Two Way Anova test with a significant level of 0.05. The results showed that: (1) mathematical critical thinking ability of students taught with the STAD type cooperative learning model was higher than mathematical critical thinking ability of students taught with the conventional learning model (Fcount = 21.164 and sig. 0.000> 0.05); (2) The mathematical critical thinking ability of students who have high social skills was higher than the mathematical critical thinking ability of students who have low social skills (Fcount = 6.756 and sig. 0.012> 0.05); and (3) There was an interaction between learning models and social skills in effecting mathematical critical thinking ability of students (Fcount = 7.054 and sig. 0.011> 0.05).